Creditor Protection in Bank Spinoffs: A Comparative Analysis of Indonesia and Vietnam - Ariq Ardiawan Alano (Legtimacy: Journal of Law and Islamic Law, 2026)
Mandatory bank spinoffs introduce systemic asset dilution risks, exposing a critical doctrinal conflict between corporate limited liability and creditor wealth maximization. Through a functional comparative legal approach, this article evaluates creditor protection frameworks under Indonesian and Vietnamese corporate regimes. The analysis reveals that the reliance of Indonesia on procedural notifications establishes a flawed fiction of tacit consent. Driven by high transaction costs and severe information asymmetry, retail creditors inevitably succumb to rational apathy, enabling opportunistic judgment proofing. Conversely, the modernized framework of Vietnam effectively internalizes transition risks by enforcing substantive joint and several liability alongside aggressive central bank interventions. This comparative study demonstrates that procedural mechanisms fail to safeguard fixed claimants against strategic corporate partitioning. Consequently, this article proposes a legislative reconstruction for Indonesia by introducing a mandatory three year joint liability retention period. This prescriptive reform eliminates moral hazard, ensures capitalization stability, and fully aligns national corporate governance standards.